Preliminary archaeometric investigation on Middle Neolithic siliceous tools from Limba-Oarda de Jos (Transylvania, Romania). (2019) - , Mar Rey-Solé; , Corina Ionescu; , Marius-Mihai Ciutӑ; , Marieta Mureșan-Pop; Simon, Viorica
No abstract available